Hydromechanism and Desalination of Coastal Karst Aquifers: Theory and Case - Breznik, Marko; Steinman, Franci (Acta Carsologica, 2008)
Brackish water of coastal karst aquifers is useless. Desalination methods are: interception method to capture fresh water in karst massif, isolation and rise-spring-level methods to prevent sea water inflow and reduced pumping of fresh water in dry periods. Four typical cases explain these methods.